2013
DOI: 10.1002/ajmg.a.35808
|View full text |Cite
|
Sign up to set email alerts
|

GPSM2 and Chudley–McCullough Syndrome: A Dutch Founder Variant Brought to North America

Abstract: Chudley-McCullough syndrome (CMS) is characterized by profound sensorineural hearing loss and brain anomalies. Variants in GPSM2 have recently been reported as a cause of CMS by Doherty et al. In this study we have performed exome sequencing of three CMS patients from two unrelated families from the same Dutch village. We identified one homozygous frameshift GPSM2 variants c.1473delG in all patients. We show that this variant arises from a shared, rare haplotype. Since the c.1473delG variant was found in Menno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…2a) (Walsh et al 2010; Yariz et al 2012; Doherty et al 2012; Diaz-Horta et al 2012; Almomani et al 2013). To study the effect of truncating mutations in GPSM2 analogous to the human variants, we utilized a mouse model containing a deletion of the C-terminal GoLoco motifs, named Lgn Δ C previously studied to examine the role of Lgn in the developing neuroepithelium (Konno et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a) (Walsh et al 2010; Yariz et al 2012; Doherty et al 2012; Diaz-Horta et al 2012; Almomani et al 2013). To study the effect of truncating mutations in GPSM2 analogous to the human variants, we utilized a mouse model containing a deletion of the C-terminal GoLoco motifs, named Lgn Δ C previously studied to examine the role of Lgn in the developing neuroepithelium (Konno et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…A strong knockdown of Lgn in murine skin causes defects in barrier function, resulting in dehydration and death (Williams et al 2011). In contrast, all reported truncating human variants in GPSM2/LGN are viable (Walsh et al 2010; Yariz et al 2012; Doherty et al 2012; Diaz-Horta et al 2012; Almomani et al 2013). …”
Section: Introductionmentioning
confidence: 90%
“…AGS4 (GPSM3), which is enriched in immune cells and regulates immune cell chemotaxis, is associated with autoimmune diseases (Cao et al, 2004;Giguere et al, 2013). AGS5, which exhibits a similar domain structure as AGS3, also plays important functional roles in asymmetric cell division and morphogenesis, and was recently identified as a responsible gene for certain types of nonsyndromic hearing loss, planar cell polarity in cochlear hair cells, and the brain malformations and hearing loss observed as part of the Chudley-McCullough syndrome (Du et al, 2001;Du and Macara, 2004;Lechler and Fuchs, 2005;Fukukawa et al, 2010;Walsh et al, 2010;Zheng et al, 2010Zheng et al, , 2013Williams et al, 2011;Yariz et al, 2012;Diaz-Horta et al, 2012;Doherty et al, 2012;Almomani et al, 2013;Ezan et al, 2013). The functional role of AGS5 and G proteins in coordinating planar cell polarity of the cochlear hair cell may involve both the PAR polarity protein complex and positioning of the kinocilium (Ezan et al, 2013).…”
Section: Activators Of G Protein Signaling (Ags Proteins)mentioning
confidence: 99%
“…Chudley-McCullough syndrome, first described in 1997 [1], is a very rare autosomal recessive disorder characterized by partial corpus callosum agenesis, colpocephaly with a right-sided tendency and bilateral severe to profound sensorineural hearing loss [1][2][3][4][5][6][7][8][9][10][11][12][13]. Other abnormalities include cortical dysplasia, frontal polymicrogyria, cerebellar dysgenesia, gray matter heterotopy, arachnoid cysts and sometimes mental retardation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the G-protein signaling modulator 2 gene (GPSM2), which produces the Leu-Gly-Asn repeat-enriched protein (LGN), were found to be responsible for the syndrome [5]. Currently, nine different mutations in the GPSM2 gene are known to cause the Chudley-McCullough syndrome [2,[4][5][6]9]. It has been suggested that GPSM2 has a role in maintaining cell polarity through effects on the orientation of the mitotic spindle, which is why a mutation may lead to aberrations in asymmetric cell divisions during development [5].…”
Section: Introductionmentioning
confidence: 99%